E-028 Intracranial Stenting without Angioplasty for Cerebral Aneurysms with Adjacent Vessel Stenoses. (14th July 2013) - Toth, G; Elgabaly, M; Bain, M; Hui, F; Hussain, M
Abstract : Introduction: Intracranial stenting is currently not routinely recommended for intracranial stenotic disease based on recent clinical trial results. However, wide-necked cerebral aneurysms with adjacent vascular stenoses may require stent placement to assist with coil embolisation. The safety and efficacy of this approach have not been well studied. Objective: We report the outcomes of intracranial stent placement and coiling in patients with wide-necked intracranial aneurysms and associated vessel stenosis. Methods: Report of 2 cases with relevant neuroimaging and literature review Results: The first female patient presented with dizziness and vertigo, and was found to have an unruptured wide-necked basilar apex aneurysm involving both posterior cerebral artery origins. In addition, there was significant atherosclerotic narrowing of the distal basilar artery, just proximal to the aneurysm. The second female patient initially presented with subarachnoid haemorrhage from a ruptured broad-based posterior communicating artery aneurysm, which was first coil embolised, but later showed recurrence requiring re-treatment. This patient also had moderate adjacent parent vessel stenosis. After a 5-day pretreatment with aspirin and clopidogrel, endovascular coiling was performed with Neuroform stent (Boston Scientific, Fremont, CA) assistance in both cases. The vascular reconstruction device covered the stenotic vessel segments. No balloon angioplasty was performed. We encountered no periprocedural complications. Both patents remained clinically asymptomatic with 6-month follow-up angiograms demonstrating stable aneurysm occlusion and improved vascular stenoses. Conclusion: Stent assisted coiling may be a feasible option for wide-necked intracranial aneurysm with associated pre-existing vascular stenoses. In our cases, Neuroform stent placement across the stenotic area was safe without in-stent stenosis, thromboembolism, ischaemia or other adverse event. These results are promising, but a larger cohort is needed to assess long-term outcome. Disclosures: G. Toth: None. M. Elgabaly: None. M. Bain: None. F. Hui: None. M. Hussain: None.